Situation Report: Romania, 18 July 1972 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Polish Foreign Minister in Bucharest Reaction to McGovern's Nomination Romania's Relations with the Developing Countries Fulfillment of Economic Plan in First Half of 1972 Measures to Improve Supplies for the Population New Orientation in Romanian Education Campaign about the Obligation to Work Six Romanian Writers Disciplined by Writers' Union Unification of Party and Administrative Functions Extended